Peran Pelaporan Keberlanjutan dan Keberagaman Gender dalam Meningkatkan Kinerja Keuangan pada Sektor Perbankan - Aris Sanulika (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
The increasing emphasis on sustainability, inclusive governance, and financial performance has intensified the need for empirical evidence in the banking sector, particularly in emerging economies such as Indonesia. Banks are no longer evaluated solely on financial outcomes but also on their commitment to transparency, social responsibility, and effective governance structures. This study aims to examine the relationship between sustainability reporting, gender diversity, intermediation efficiency, capital adequacy, firm age, and financial performance in Indonesian conventional banks. The research adopts a quantitative approach with an associative research design. The population comprises all banking companies operating in Indonesia, while the sample is selected using purposive sampling based on predetermined criteria, resulting in twenty-eight conventional banks observed over the period from two thousand eighteen to two thousand twenty-four. Panel data regression is employed as the analytical method, supported by panel model selection tests, classical assumption tests, and hypothesis testing. Data processing is conducted using EViews software. The findings indicate that sustainability reporting, gender diversity, and intermediation efficiency play a significant role in enhancing bank profitability. Sustainability reporting functions as a strategic mechanism to strengthen stakeholder trust, improve transparency, and reinforce corporate legitimacy. Gender diversity contributes to better decision-making quality and more effective corporate governance. In contrast, capital adequacy and firm age show relatively limited influence. Overall, the study highlights the strategic importance of inclusive governance and sustainable practices in improving the financial performance of the Indonesian banking sector.